Visfatin and Adiponectin Have an Opposite Correlation with Inflammation and Metabolic Syndrome in Non-Diabetic Obese Indonesian Men - Anna Meiliana; Gatot Susilo Lawrence; Ilhamjaya Patellongi; Andi Wijaya; Suryani As'ad (The Indonesian Biomedical Journal, 2009)
BACKGROUND: Along with the increase in obesity is a parallel increase in the prevalence of metabolic complications of obesity, often referred to as the metabolic syndrome (MetS). The role of adipose tissue in MetS has continued to evolve with the description of numerous secretory peptides from adipocytes named adipocytokines or adipokines. Recent studies have found visfatin as the regulation of inflammatory and immunomodulating prosesses, meanwhile adiponectin was known to have a potent anti-inflammatory properties. Here we try to assess the correlation between those two adipokines to MetS, via an inflammatory pathway.METHODS: This was a cross-sectional study on 128 non diabetic obese male subject (waist circumferences ≥90 cm). Visfatin and adiponectin were assessed by ELISA. Statistical analysis was performed using SPSS for Windows v.16.00 with signifcantly p<0.05. The correlations among biomarkers were assessed using Spearman's Rho test.RESULTS: This study showed a significant positive correlation between levels of visfatin and inflammatory markers TNF-α (r=0.22, p<0.005), and hsCRP (r=0.12, p=0.19), significant negative correlation between levels of adiponectin and TNF-α (r=-0.22-8, p<0.005-1), adiponectin and hsCRP (r=-0.14, p=0.11) and visfatin (r=-0.029, p<0.01). Plasma visfatin levels were increased along with the number MetS components, white plasma adiponectin showed inversely relation.CONCLUSION: Our present study has shown that visfatin has a proinflammatory properties and adiponectin has an anti-inflammatory properties, and how they have an opposite effects on MetS. Visfatin was found to have a positive correlaton while adiponectin was found to have a negative correlation with the number of MetS components.KEYWORDS: Obesity, Inflammation, Metabolic Syndrome, Adipocytokines, Visfatin, Adiponectin, TNF-α, hsCRP